Pengaruh Spesialisasi Auditor, Audit Tenure, Leverage dan Profitabilitas terhadap Manajemen laba pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia - Febianita Ayu Larassati; Hasim As'ari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of testing this research is to find out whether Auditor Industry Specialization, Audit Tenure, Leverage and Profitability have an influence on the occurrence of Earnings Management in Food and Beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2019 to 2021. Food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange which will be the focus of the population for this study and the data needed is obtained from their financial statements. Sampling was carried out using several criteria with the purposive sampling method for sample selection. Sample data obtained from 16 companies with a period of 2019 to 2021. SPSS version 26 is used for data analysis then continued with classical assumption testing then hypothesis testing with partial tests. This study found that auditor industry specialization, audit tenure, and leverage do not affect earnings management and profitability has a positive impact on earnings management.